A refractory material and a method for preparing the same

By using composite flame retardant fillers and functional adhesives in refractory materials, the problems of powdering and cracking of traditional refractory materials at high temperatures are solved, the flame retardant and sealing performance is improved, the service life is extended and the risk of equipment damage is reduced. .

CN118637860BActive Publication Date: 2024-12-13YANTAI JINRUN NUCLEAR POWER MATERIAL CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411095324.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-12
Publication Date
2024-12-13
Estimated Expiration
2044-08-12

AI Technical Summary

Technical Problem

Traditional refractory materials are prone to powdering, cracking or falling off in long-term high temperature environments, resulting in a degradation of sealing performance and difficulty meeting the needs of use under various conditions, increasing the risk of equipment damage and casualties.

Method used

Compound flame retardant filler and functional binder are used to prepare composite flame retardant filler by Michael addition reaction of modified aluminum hydroxide and 3-aminophenylboric acid, and esterification and radical polymerization of phenolic resin and eugenol. Prepare functional adhesives, combined with vinyl phenyl silicone oil and hydroxy silicone oil, to form refractory materials to enhance flame retardant and sealing properties.

Benefits of technology

It significantly improves the flame retardant capacity and cohesion of refractory materials, avoids fire spread, powderization, cracking, enhances sealing performance and service life, and provides better fire protection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118637860B_ABST
    Figure CN118637860B_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of refractory materials, and discloses a refractory material and a preparation method thereof. The refractory material comprises the following raw materials: a refractory filler, an expansion filler, a composite flame retardant filler, a modifier, vinylphenyl silicone oil, hydroxy silicone oil, a functional adhesive, and a reinforcing filler. The invention prepares the composite flame retardant filler and the functional adhesive to participate in the preparation process of the refractory material, so that the prepared refractory material has dual flame retardancy, strong fire resistance and fire prevention ability, strong cohesion, can effectively prevent the spread of fire in actual use, protect life and property safety, is not prone to powdering, cracking and falling off, has good sealing performance, makes the content not easy to leak, has excellent protection effect on equipment, effectively reduces equipment maintenance cost, prolongs the service life of equipment, and has a long service life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of refractory materials, and in particular to a refractory material and a preparation method thereof. Background Art

[0002] Refractory materials are materials that can maintain structural stability at high temperatures and withstand corresponding physical and chemical changes and mechanical effects. They play a vital role in the field of high-temperature industries. With the rapid development of high-temperature industries, refractory materials are widely used in the fields of sealing and protection of equipment, improving the sealing of pipelines, preventing leakage of pipeline contents, and ensuring the safe operation of equipment. However, the cohesion of traditional refractory materials is average after long-term use. Thermal stress and oxidation will cause the refractory materials to crack, powder or fall off, making it difficult to maintain the stability of the sealing layer structure. The failure of the sealing protection will cause leakage of contents, resulting in equipment damage and increased maintenance costs. In long-term high-temperature environments, there is a risk of fire inside or outside the equipment, and the flame retardant properties of traditional refractory materials are difficult to meet the use requirements under various conditions. There is a risk of fire spreading and causing equipment damage and casualties.

[0003] Therefore, at present, when using refractory materials, people usually improve them. For example, the patent with announcement number CN103642244B discloses a flame retardant refractory material and a preparation method. The prepared product has good mechanical properties, flame retardant properties and electrical properties. It can form a hard shell when a fire occurs and form a dense fireproof layer above 600°C. At the same time, when zinc oxide is added, the flame retardant and fire resistant properties of the product can be greatly improved. The flame retardant and fireproof properties are excellent, but the material has insufficient cohesion under long-term high temperature environment, and its anti-aging ability needs to be improved. When used for a long time, it is easy to powderize, crack and other phenomena, which have an adverse effect on the flame retardant and sealing properties of the refractory material. Summary of the invention

[0004] The purpose of the present invention is to provide a refractory material and a preparation method thereof, which solves the problem that traditional refractory sealing materials are prone to powdering, cracking and even falling off after long-term use, and the fire retardant ability is difficult to meet the use requirements under various conditions.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] A refractory material comprises the following raw materials in parts by weight: 20-30 parts of refractory filler, 8-10 parts of expansion filler, 5-8 parts of composite flame retardant filler, 2-5 parts of modifier, 15-20 parts of vinyl phenyl silicone oil, 8-12 parts of hydroxy silicone oil, 20-25 parts of functional adhesive and 5-10 parts of reinforcing filler.

[0007] Furthermore, the refractory filler is any one of hollow glass microspheres and kaolin; the expandable filler is any one of expanded graphite, expanded mullite and expanded vermiculite; the modifier is a silane coupling agent; and the reinforcing filler is any one of nano calcium carbonate and white carbon black.

[0008] Furthermore, the preparation method of the composite flame retardant filler comprises the following steps:

[0009] S1: vinylphosphonic acid is placed in deionized water, and after being fully mixed, aluminum hydroxide is added, the temperature is raised to 90-95°C, and the mixture is fully stirred for 6-8 hours, and the product is collected to obtain modified aluminum hydroxide;

[0010] S2: Place modified aluminum hydroxide and 3-aminophenylboronic acid in tetrahydrofuran, stir thoroughly, add a catalyst, raise the temperature to 55-60°C and react for 3-5 hours. After the reaction, collect the product to obtain a composite flame retardant filler.

[0011] In this scheme, the phosphoric acid group in the vinylphosphonic acid structure interacts with the hydroxyl group on the surface of aluminum hydroxide to obtain an organic phosphorus-coated modified aluminum hydroxide, and then under the action of a catalyst, the double bond in the modified aluminum hydroxide structure reacts with the amino group in the 3-aminophenylboronic acid structure to produce a Michael addition reaction to obtain a composite flame retardant filler. This composite flame retardant filler is an inorganic-organic composite flame retardant with a double-layer flame retardant effect. The inner aluminum hydroxide layer undergoes an endothermic decomposition reaction at high temperature, absorbs a large amount of heat, and reduces the material temperature. The outer organic phosphorus layer can decompose to produce strong acid and carbon layer to inhibit combustion. Nitrogen elements can produce non-combustible gas, dilute the gas to reduce the intensity of combustion, and boron elements can promote the formation of carbon layer and improve structural stability. The three cooperate with each other and work together to enhance the carbon layer to effectively isolate the transfer of heat and oxygen, improve the flame retardant efficiency, and participate in the preparation process of refractory materials. When the refractory materials are used, they can effectively play a flame retardant role and significantly improve the flame retardant ability of refractory materials.

[0012] Furthermore, in step S1, the usage ratio of vinylphosphonic acid, deionized water and aluminum hydroxide is 3-4g:70-90ml:1.5-2.5g.

[0013] Furthermore, in step S1, the average particle size of the aluminum hydroxide is 1.5 μm.

[0014] Furthermore, in step S2, the usage ratio of the modified aluminum hydroxide, 3-aminophenylboric acid, tetrahydrofuran and catalyst is 2.6-3.8 g: 3-4 g: 80-120 ml: 0.02-0.05 g.

[0015] Furthermore, in step S2, the catalyst is triethylamine.

[0016] Furthermore, the preparation method of the functional adhesive comprises the following steps:

[0017] SS1: Phenolic resin and rosin acid are placed in N,N-dimethylformamide, and p-toluenesulfonic acid is added after being fully stirred and mixed. The temperature is raised to react, and the solvent is removed by rotary evaporation. The product is collected to obtain a modified phenolic resin;

[0018] SS2: Place the modified phenolic resin in acetone, add eugenol, mix thoroughly, add initiator, heat to 45-50°C and react for 6-8h, collect the product after reduced pressure distillation to obtain a functional adhesive.

[0019] In this scheme, the hydroxyl group in the phenolic resin structure and the carboxyl group in the rosin acid structure undergo esterification reaction under the action of p-toluenesulfonic acid to obtain a modified phenolic resin containing a tricyclic phenanthrene skeleton in the structure, and then under the action of an initiator, the double bonds in the modified phenolic resin structure undergo free radical polymerization reaction with the double bonds in the eugenol structure to obtain a functional adhesive. The tricyclic phenanthrene skeleton in the structure of this functional adhesive can enhance the bonding strength of the adhesive, and the eugenol introduced in its structure has an excellent antioxidant effect, and the antioxidant small molecules are grafted into the macromolecular structure in a chemically bonded manner, which can effectively prevent the small molecules from precipitating during long-term use, so that it can better play an antioxidant effect, and the adhesive is involved in the preparation process of the refractory material, which can enhance the adhesion between the components of the refractory material, enhance cohesion, and improve sealing performance, and when used for a long time, the refractory material cohesion caused by insufficient adhesive bonding strength and accelerated aging process at high temperature will not be reduced, thereby causing cracking, powdering, or even falling off, so that the refractory material has more excellent sealing performance and a long service life.

[0020] Furthermore, in step SS1, the usage ratio of the phenolic resin, rosin acid, N,N-dimethylformamide and p-toluenesulfonic acid is 3-5g:3.5-4.2g:60-100ml:0.1-0.3g.

[0021] Furthermore, in step SS1, the temperature of the temperature-raising reaction is 105-115° C., and the time is 5-8 hours.

[0022] Furthermore, in step SS2, the usage ratio of the modified phenolic resin, acetone, eugenol and initiator is 4-4.5 g:50-80 ml:3-4 g:0.4-0.8 g.

[0023] Furthermore, in step SS2, the initiator is any one of benzoyl peroxide and diisopropylbenzene peroxide.

[0024] A method for preparing a refractory material comprises the following steps:

[0025] Step 1: placing a refractory filler, an intumescent filler, a composite flame retardant filler and a modifier in a mixer, and mixing them thoroughly to obtain a premix;

[0026] Step 2: Place vinyl phenyl silicone oil, hydroxy silicone oil, functional adhesive, and reinforcing filler in a blender and mix for 1-1.5 hours to obtain a bonding material;

[0027] Step three, after the premix and the binder are fully mixed, they are extruded through a twin-screw extruder to obtain a refractory material.

[0028] Beneficial effects of the present invention:

[0029] The present invention prepares composite flame-retardant fillers and functional adhesives in the preparation process of refractory materials, so that the prepared refractory materials have dual flame retardancy, strong fire resistance and fire prevention ability, strong cohesion, can effectively prevent the spread of fire in actual use, and are not easy to pulverize, crack and fall off, have good sealing performance, have excellent protection for equipment, and have a long service life. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.

[0031] Figure 1 The present invention is a flow chart for preparing the refractory material. DETAILED DESCRIPTION

[0032] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0033] The preparation of the composite flame retardant filler and the functional adhesive in the following examples and comparative examples of the present invention is as follows:

[0034] 1. Preparation of composite flame retardant filler

[0035] S1: 3.5 g of vinylphosphonic acid was placed in 80 ml of deionized water, and after thorough mixing, 2 g of aluminum hydroxide with an average particle size of 1.5 μm was added, the temperature was raised to 90° C., and the mixture was thoroughly stirred for 6 h. The product was collected to obtain modified aluminum hydroxide;

[0036] S2: 3 g of modified aluminum hydroxide and 3.6 g of 3-aminophenylboronic acid were placed in 100 ml of tetrahydrofuran, stirred thoroughly, 0.03 g of triethylamine was added, the temperature was raised to 55° C. and the reaction was carried out for 3 h. After the reaction, the product was collected to obtain a composite flame retardant filler.

[0037] The modified aluminum hydroxide and composite flame retardant filler were analyzed for nitrogen element using EMA 502 organic element analyzer. The analysis showed that the modified aluminum hydroxide did not contain nitrogen element; the nitrogen content in the composite flame retardant filler was 3.6%. The appearance of nitrogen element indicated that the double bond in the modified aluminum hydroxide structure and the amino group in the 3-aminophenylboronic acid structure underwent Michael addition reaction to obtain a composite flame retardant filler containing nitrogen element.

[0038] 2. Preparation of functional adhesives

[0039] SS1: 4 g of phenolic resin and 3.8 g of rosin acid were placed in 80 ml of N,N-dimethylformamide, and 0.2 g of p-toluenesulfonic acid was added after thorough stirring and mixing. The temperature was raised to 105°C for reaction for 5 h, and the solvent was removed by rotary evaporation. The product was collected to obtain a modified phenolic resin;

[0040] The modified phenolic resin was used as a sample, and the double bond content in its structure was tested by iodine titration. 25 ml of carbon tetrachloride was placed in an iodine volumetric flask, 1 g of sample and 12 ml of potassium bromide were added, and after shaking, 5 ml of 10% potassium iodide solution and 6 ml of distilled water were added and shaken. A 0.1 mol / L sodium thiosulfate standard solution was used for titration. When the color changed, 1 ml of 1% starch solution was added, and the titration was continued to the reaction end point. A blank control was also performed. The double bond content in the sample was calculated by referring to the following formula: W=(V0−V1)c×0.05×74 / M; where W is the double bond content in the sample, %; V0 is the volume of sodium thiosulfate consumed in the blank test, ml; V1 is the volume of sodium thiosulfate consumed by the titrated sample, ml; and c is the concentration of the sodium thiosulfate solution, mol / L. After calculation, the double bond content in the modified phenolic resin is 7.9%.

[0041] SS2: 4.2 g of modified phenolic resin was placed in 60 ml of acetone, 3.5 g of eugenol was added, and after thorough mixing, 0.6 g of benzoyl peroxide was added, and the temperature was raised to 45 °C for reaction for 6 h. The product was collected after reduced pressure distillation to obtain a functional adhesive.

[0042] The functional adhesive was used as a sample and the double bond content in its structure was detected using the iodine titration method. The specific steps were the same as SS1. After testing, the double bond content in the functional adhesive was 1.8%. The loss was due to the free radical polymerization reaction between the double bonds in the modified phenolic resin structure and the double bonds in the eugenol structure.

[0043] With reference to the standard GB / T2792-2014, the peel strength test of phenolic resin, modified phenolic resin and functional adhesive was carried out. After testing, the peel strength of phenolic resin was 11.7N / 25mm; the peel strength of modified phenolic resin was 14.5N / 25mm; the peel strength of functional adhesive was as high as 14.8N / 25mm, which shows that modified phenolic resin and functional adhesive have better bonding properties; phenolic resin, modified phenolic resin and functional adhesive were placed in an aging box at 80℃ for 24h, and the peel strength was tested again. The peel strength of phenolic resin was 7.5N / 25mm; the peel strength of modified phenolic resin was 11.4N / 25mm; the peel strength of functional adhesive was as high as 13.2N / 25mm, which shows that functional adhesive has better anti-aging ability. Example 1

[0044] Preparation of refractory materials

[0045] Step 1, placing 20 g of hollow glass microspheres, 8 g of expanded graphite, 5 g of composite flame retardant filler, and 2 g of vinyl triethoxysilane in a mixer, and mixing them thoroughly to obtain a premix;

[0046] Step 2: 15 g of vinyl phenyl silicone oil, 8 g of hydroxy silicone oil, 20 g of functional adhesive, and 5 g of nano calcium carbonate were placed in a blender and mixed for 1 hour to obtain a bonding material;

[0047] Step three, after the premix and the binder are fully mixed, they are extruded through a twin-screw extruder to obtain a refractory material. Example 2

[0048] Preparation of refractory materials

[0049] Step 1: Place 25 g of hollow glass microspheres, 9 g of expanded mullite, 7 g of composite flame retardant filler, and 3 g of allyltrimethoxysilane in a mixer and mix thoroughly to obtain a premix;

[0050] Step 2: 18 g of vinyl phenyl silicone oil, 10 g of hydroxy silicone oil, 22 g of functional adhesive, and 8 g of nano calcium carbonate were placed in a blender and mixed for 1.2 h to obtain a bonding material;

[0051] Step three, after the premix and the binder are fully mixed, they are extruded through a twin-screw extruder to obtain a refractory material. Example 3

[0052] Preparation of refractory materials

[0053] Step 1: Place 30 g of kaolin, 10 g of expanded vermiculite, 8 g of composite flame retardant filler, and 5 g of allyltriethoxysilane in a mixer, and mix them thoroughly to obtain a premix;

[0054] Step 2: 20 g of vinyl phenyl silicone oil, 12 g of hydroxy silicone oil, 25 g of functional adhesive and 10 g of white carbon black were placed in a blender and mixed for 1.5 h to obtain a bonding material;

[0055] Step three, after the premix and the binder are fully mixed, they are extruded through a twin-screw extruder to obtain a refractory material.

[0056] Comparative Example 1

[0057] Preparation of refractory materials

[0058] Step 1, placing 25 g of hollow glass microspheres, 9 g of expanded mullite, 7 g of aluminum hydroxide, and 3 g of allyltrimethoxysilane in a mixer, and mixing them thoroughly to obtain a premix;

[0059] Step 2: 18 g of vinyl phenyl silicone oil, 10 g of hydroxy silicone oil, 22 g of functional adhesive, and 8 g of nano calcium carbonate were placed in a blender and mixed for 1.2 h to obtain a bonding material;

[0060] Step three, after the premix and the binder are fully mixed, they are extruded through a twin-screw extruder to obtain a refractory material.

[0061] Comparative Example 2

[0062] Preparation of refractory materials

[0063] Step 1: Place 25 g of hollow glass microspheres, 9 g of expanded mullite, 7 g of composite flame retardant filler, and 3 g of allyltrimethoxysilane in a mixer and mix thoroughly to obtain a premix;

[0064] Step 2: 18 g of vinyl phenyl silicone oil, 10 g of hydroxy silicone oil, 22 g of phenolic resin, and 8 g of nano calcium carbonate were placed in a blender and mixed for 1.2 h to obtain a bonding material;

[0065] Step three, after the premix and the binder are fully mixed, they are extruded through a twin-screw extruder to obtain a refractory material.

[0066] Comparative Example 3

[0067] Preparation of refractory materials

[0068] Step 1: Place 25 g of hollow glass microspheres, 9 g of expanded mullite, 7 g of composite flame retardant filler, and 3 g of allyltrimethoxysilane in a mixer and mix thoroughly to obtain a premix;

[0069] Step 2: 18 g of vinyl phenyl silicone oil, 10 g of hydroxy silicone oil, 22 g of modified phenolic resin, and 8 g of nano calcium carbonate were placed in a blender and mixed for 1.2 h to obtain a bonding material;

[0070] Step three, after the premix and the binder are fully mixed, they are extruded through a twin-screw extruder to obtain a refractory material.

[0071] Performance Testing

[0072] The fire resistance level and air tightness of the refractory materials prepared in Example 1 to Example 3 and Comparative Example 1 to Comparative Example 3 were tested as samples with reference to the standard GB23864-2003; the flame retardant level of the samples was tested with reference to the UL-94 standard; the samples were immersed in water, and the number of days when the samples swelled or cracked was recorded to judge the water resistance of the samples; the samples were placed in an aging box at 80°C for 24 hours, and the surface morphology of the samples, i.e., cracking or powdering, was observed; the specific test results are shown in the following table:

[0073] Fire resistance level / h <![CDATA[Air tightness / m 3 / (m·h)]]> Flame retardant grade Water resistance / d Appearance Example 1 3 <3 V-0 5 No change Example 2 3 <3 V-0 5.5 No change Example 3 3 <3 V-0 5 No change Comparative Example 1 3 <3.5 V-1 5 No change Comparative Example 2 2 >3.5 V-0 4 Cracking and powdering Comparative Example 3 3 <3.5 V-0 4 No cracks, powdering

[0074] As can be seen from the above table, the samples prepared in Examples 1 to 3 all have good comprehensive performance, good fire resistance and air tightness, high flame retardant grade, strong water resistance and good anti-aging ability, and are not easy to powderize and fall off. Comparative Example 1 does not contain a composite flame retardant, and aluminum hydroxide is directly added. Comparative Example 2 does not contain a functional adhesive, and a phenolic resin is directly added. Comparative Example 3 does not contain a functional adhesive, and a modified phenolic resin is added. It can be seen that the flame retardant performance of Comparative Example 1 is general, and the fire resistance grade, air tightness, water resistance and aging resistance of Comparative Example 2 are significantly reduced compared with the examples, because the directly added phenolic resin has insufficient bonding strength, resulting in general cohesion of the refractory material and weak adhesion. Compared with the examples, Comparative Example 3 has a powdering phenomenon because the modified phenolic resin is directly added without the addition of an antioxidant.

[0075] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0076] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the scope defined by the concept of the invention, they should all fall within the protection scope of the present invention.

Claims

1. A refractory material, characterized in that: The invention comprises the following raw materials in parts by weight: 20-30 parts of refractory filler, 8-10 parts of expansion filler, 5-8 parts of composite flame retardant filler, 2-5 parts of modifier, 15-20 parts of vinylphenyl silicone oil, 8-12 parts of hydroxy silicone oil, 20-25 parts of functional adhesive, and 5-10 parts of reinforcing filler; The preparation method of the composite flame retardant filler comprises the following steps: S1: vinylphosphonic acid is placed in deionized water, mixed thoroughly, and then aluminum hydroxide is added. The temperature is raised to 90-95°C, and the mixture is stirred thoroughly for 6-8 hours. The product is collected to obtain modified aluminum hydroxide; S2: Place modified aluminum hydroxide and 3-aminophenylboronic acid in tetrahydrofuran, stir thoroughly, add a catalyst, raise the temperature to 55-60°C, react for 3-5 hours, and collect the product to obtain a composite flame retardant filler; The preparation method of the functional adhesive comprises the following steps: SS1: Phenolic resin and rosin acid are placed in N,N-dimethylformamide, stirred thoroughly, and then p-toluenesulfonic acid is added. The temperature is raised to react, and the solvent is removed by rotary evaporation. The product is collected to obtain a modified phenolic resin; SS2: Place the modified phenolic resin in acetone, add eugenol, mix thoroughly, add initiator, heat to 45-50°C and react for 6-8 hours. Collect the product after reduced pressure distillation to obtain a functional adhesive; The refractory filler is any one of hollow glass microspheres and kaolin; the expandable filler is any one of expanded graphite, expanded mullite, and expanded vermiculite; the modifier is a silane coupling agent; the reinforcing filler is any one of nano calcium carbonate and white carbon black; The catalyst is triethylamine.

2. A refractory material according to claim 1, characterized in that: In step S1, the average particle size of the aluminum hydroxide is 1.5 μm.

3. A refractory material according to claim 1, characterized in that: In step SS1, the temperature of the temperature-raising reaction is 105-115° C., and the time is 5-8 hours.

4. A refractory material according to claim 1, characterized in that: In step SS2, the initiator is any one of benzoyl peroxide and dicumyl peroxide.

5. A method for preparing a refractory material according to claim 1, characterized in that: The following steps are involved: Step 1: placing a refractory filler, an intumescent filler, a composite flame retardant filler, and a modifier in a mixer and mixing them thoroughly to obtain a premix; Step 2: vinylphenyl silicone oil, hydroxy silicone oil, functional adhesive, and reinforcing filler are placed in a blender and mixed for 1-1.5 hours to obtain an adhesive; Step 3: After the premix and the binder are fully mixed, they are extruded through a twin-screw extruder to obtain a refractory material.

Citation Information

Cited By

  • Novel efficient fire-resistant heat insulation plate for nuclear power and preparation method thereof

    CN122233748A